Names and the prevention of the suspicion of the prohibition of using them - Abdelfattah, Fatima Eid (Journal of Humanities & Social Sciences, 2021)
The study was based on addressing the problem for which it was based, which is to prevent the fatwa prohibiting names from a linguistic point of view and to show their sincerity, so they had to start with an introduction through which the problem of study and its importance and method of conduct emerged and then followed by five investigations through which it clarified in the first research the knowledge of the name and name and the manifestation of confusion between them and then the second research- science and its provisions, followed by the third research- sections of science with its various considerations to reach the fourth research- transferred science and the names improvised emerged through the definition of The science transmitted, the aspects on which it comes, and the rule of science after transfer from its meaning to the scientific. The definition of improvised science, its types, and then the purpose of combining AL with science, the excess AL. Then came the fifth research- concerning the fatwa of prohibition and included: clarifying the terminator of names, presenting some of the sites that mentioned names and prohibiting them, and then clarifying three examples of the names contained in the fatwa: then the study ended with a conclusion that included its results, which showed the insincerity of the fatwa prohibiting some names and using them in Arabic.